Suppression of Meloidogyne javanica by antagonistic and plant growth-promoting rhizobacteria - Li, Bin (Zhejiang University Press, 2005)

(untitled)
Four rhizobacteria selected out of over 500 isolates from rhizosphere of the vegetables in China were further studied for suppression of the root-knot nematode and soil-borne fungal pathogens in laboratory and greenhouse in Belgium. They were identified as Brevibacillus brevis or Bacillus subtilis by Biolog test and partial 16s rDNA sequence comparison. They not only inhibited the radial growth of the root-infecting fungi Rhizoctonia solani SX-6, Pythium aphanidermatum ZJP-1 and Fusarium oxysporum f.sp. cucumerinum ZJF-2 in vitro, but also exhibited strong nematicidal activity by killing the second stage larvae of Meloidogyne javanica to varying degrees in the greenhouse. The toxic principles of bacterium B7 that showed the highest juvenile mortality were partially characterized. The active factors were heat stability and resistance to extreme pH values. B7 used either as seed dressing or soil drench significantly reduced the nematode populations in the rhizosphere and enhanced the growth of mungbean plants over the controls in the presence or absence of R. solani.